Confinement Effects On Spin-Orbit Activated Interchannel Coupling. (August 2015) - Keating, David A; Deshmukh, P C; Manson, Steven T
Synopsis: The spin-orbit activated interchannel coupling is a purely relativistic effect that alters the partial photoionization cross sections of spin-orbit doublet channels. Presented is an exploration of how the spin-orbit activated interchannel coupling is affected by confinement in a C60 cage.